Adaptation and evaluation of an intervention to reduce loneliness amongst adults with depression - Hare-Duke, Laurie (2020)
Loneliness is highly prevalent amongst adults with mental disorders and tackling loneliness is a policy priority in the United Kingdom. This thesis builds the evidence base for an intervention to reduce loneliness amongst adults accessing NHS secondary care services for depression. Loneliness was targeted using a psychosocial intervention to increase social connectedness. The aims of this thesis were to adapt an existing intervention called Groups4Health for adults (18-65) with depression, and to evaluate the feasibility of delivering this adapted intervention in a future clinical trial.